2018
DOI: 10.3171/2017.5.jns161882
|View full text |Cite
|
Sign up to set email alerts
|

A computational fluid dynamics simulation framework for ventricular catheter design optimization

Abstract: In this research an optimization methodology and 3D computational fluid dynamics algorithm were coupled to reach an important design objective for ventricular catheters: uniform inlet flow distribution. The optimized catheter design presented significantly improves on previous designs explored in the literature and on standard catheter designs used clinically. The automated, iterative fluid simulation framework described in this work can be used to rapidly explore design parameter influence on other flow-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In support of their hypothesis, the authors state that obstructing tissue is found most frequently around the most downstream set of holes in explanted catheters, yet clear evidence for this claim is currently lacking. However, based on this hypothesis, multiple studies have attempted to homogenize the flow rate distribution across catheter holes by changing the catheter hole geometry [29,37,47] in an effort to decrease the probability of aspirating bulk tissue and cells at a given hole. By contrast, based on the response of astrocytes to long-term shear flow, we set the design objective for ventricular catheters to maximizing wall shear stress across the inner surfaces of a catheter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In support of their hypothesis, the authors state that obstructing tissue is found most frequently around the most downstream set of holes in explanted catheters, yet clear evidence for this claim is currently lacking. However, based on this hypothesis, multiple studies have attempted to homogenize the flow rate distribution across catheter holes by changing the catheter hole geometry [29,37,47] in an effort to decrease the probability of aspirating bulk tissue and cells at a given hole. By contrast, based on the response of astrocytes to long-term shear flow, we set the design objective for ventricular catheters to maximizing wall shear stress across the inner surfaces of a catheter.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we considered a case where the cerebral ventricles are so enlarged that frictional loss from the ventricular wall is negligible. We ensured this condition in the simulation by enclosing the ventricular catheter into a box domain whose walls are sufficiently distant from the catheter (figure 8), which also meets the distance condition suggested by Weisenberg et al [29]. We imposed a constant normal velocity condition on the surface of the domain that faces the tip of the catheter and zero-pressure condition on the outlet of the catheter.…”
Section: Formation Of Low Wall Shear Stress Zone In Typical Ventricular Cathetermentioning
confidence: 98%